Evaluation of the RUBY modular QA phantom for planar and non‐coplanar VMAT and stereotactic radiations. Issue 10 (14th August 2020) - Poppinga, Daniela; Kretschmer, Jana; Brodbek, Leonie; Meyners, Jutta; Poppe, Bjoern; Looe, Hui Khee
Abstract: Purpose: This study evaluates the clinical use of the RUBY modular QA phantom for linac QA to validate the integrity of IGRT workflows including the congruence of machine isocenter, imaging isocenter, and room lasers. The results have been benchmarked against those obtained with widely used systems. Additionally, the RUBY phantom has been implemented to perform system QA (End‐to‐End testing) from imaging to radiation for IGRT‐based VMAT and stereotactic radiations at an Elekta Synergy linac. Material and Methods: The daily check of IGRT workflow was performed using the RUBY phantom, the Penta‐Guide, and the STEEV phantom. Furthermore, Winston–Lutz tests was carried out with the RUBY phantom and a ball‐bearing phantom to determine the offsets and the diameters of the isospheres of gantry, collimator, and couch rotations, with respect to the room lasers and kV‐imaging isocenter. System QA was performed with the RUBY phantom and STEEV phantom for eight VMAT treatment plans. Additionally, the visibility of the embedded objects within these phantoms in the images and the results of CT and MR image fusions were evaluated. Results: All systems used for daily QA of IGRT workflows show comparable results. Calculated shifts based on CBCT imaging agree within 1 mm to the expected values. The results of the Winston–Lutz test based on kV imaging (2D planar and CBCT) or room lasers are consistent regardless of the system tested. The point dose values in the RUBY phantom agree to the expected values calculated using algorithms in Masterplan and Monte Carlo engine in Monaco within 3% of the clinical acceptance criteria. Conclusion: All the systems evaluated in this study yielded comparable results in terms of linac QA and system QA procedures. A system QA protocol has been derived using the RUBY phantom to check the IGRT‐based VMAT and stereotactic radiations workflow at an Elekta Synergy linac.